The role of satisfaction and involvement in perceived value and behavioral intention relationship: a test of multiple mediation model in Malaysia green hotels / Rasidah Hamid - Hamid, Rasidah (2017)
Green Hotel is an alternative tourism product that has the potential to attract guests due to a marked global environmental concern worldwide that allow guests to value, feel and involve, about the way of environmental sustainability behavioral measures. Nevertheless, compared to other special interest tourism products, research on guest behavioral intention in green hotel segment has been neglected. This study fills this void by investigating these remarkably distinctive tourism experiences through the concept of guests' perceived value. The purpose of this study was to test a model of guest's perceived value of green hotel to explain the role of satisfaction and involvement in behavioral intentions. At the theoretical level, this study aimed to demonstrate that the conventional paradigm of perceived value, satisfaction and behavioral intentions is inadequate to explain guest's behavioral intentions in the context of special interest of green hotel. A more realistic explanation is required that incorporates involvement characteristic as a potentially mediating variable. The theoretical framework for this study included five dimensions of perceived value. Empirical assessment of the theoretical framework included a survey of 325 certified green hotel guests in Malaysia. The resulting data were analyzed using the Partial Least Square methods (i.e. PLS-SEM). In this assessment, convergent and discriminant validity were performed initially on the measurement models followed by structural model. This finding of the study contributed to advancing understanding of green hotel guests and hotel industry in many ways. First, the results of the study indicated support for a multi-dimensional construct of perceived value in green hotel in relation to guest satisfaction. The most important dimension was found to be functional value (price) and functional value (social). The results indicated that green hotel guest was motivated by desire to value strong environmental effort regardless of the price offerings. The guest willingness to pay higher for green have helped the developing country such as Malaysia to put the green sustainable initiatives in place. Seconds, the results of the study indicate support for a multi-dimensional construct of perceived value in green hotel in relation to guest involvement. The most important dimension in this relationship was found to be functional value (price) and functional value (epistemic). The results indicated that green hotel guest was motivated by desire to value strong environmental effort regardless of the price offerings. Third, the result contributed to improving understanding the underlying relationship between satisfaction and involvement towards perceived value and guest's future behavioral intentions. The results showed that the perceived value, satisfaction and involvement has a significant direct effect towards behavioral intentions. Providers and marketers should disregard the traditional assumptions that all guests are similar, which results in management, operations and marketing strategies that treat guests as a homogenous whole. Finally, the results provided strong evidence of the multiple moderating effect of satisfaction and involvement relationship between perceived value dimensions and behavioral intentions. This study contributed to guest behavior and marketing literature by adding new empirical evidence on the direct and indirect relationship between perceived value, satisfaction, involvement and behavioral intentions.